Cross-Sectional Analysis of Rayon Fiber Exposure and Lung Function Among Weavers in Pemalang, Indonesia - Sulistiyani; Mursid Raharjo; Nikie Astorina Yunita Dewanti; Retno Murwani; Muhammad Auliya Rahman (JURNAL KESEHATAN LINGKUNGAN, 2026)
Introduction: Sarung Goyor is one of the popular textile industries in Indonesia. The manual production process results in the release of a high number of dust particles into the air, including rayon fibers, which are a major component of the fabric. Inhaling fine fibers causes respiratory tract irritation and impaired lung function. There hasn't been much research exploring rayon dust exposure related to small-scale weaving crafts. This study aims to find a relationship between rayon fibers and lung function among sarong weavers in Indonesia. Methods: A cross-sectional study was carried out at the Sarung Goyor Industry Center North Wanarejan, Pemalang, involving 101 male weavers. The data collected includes total dust and inhalable dust levels, lung function values, and ventilation area.Dust sampling was performed using the Hi-Q HVP-2000 and SKC PCXR 8000, and lung function values were measured using the Spiro LAB III according to ATS standards. Data were analyzed using the Kolmogorov-Smirnov test and correlation test. Results and Discussion: 78% of respondents experienced impaired lung function, obstructive 22%, restrictive 46.5%, and mixed 18.8%. There is a strong relationship between age and restriction (p = 0.001) as well as inhaled dust and restriction (p = 0.026). A statistically significant inverse association was identified between ventilation area and the presence of obstructions. Conclusion: Rayon has a significant impact on lung function, causing restriction and obstruction over time. Therefore, it is essential to advocate for improved workplace ventilation and the consistent use of protective masks among weavers.